(untitled) (American International Journal of Education and Linguistics Research, 2022)
Online education is getting popularity in the last few decades and the pandemic “Covid 19” has fostered this education activities working from distant places around the world including Bangladesh. Technology is the key innovation of the 21st century which has a great influence upon every sector of human life. People in the last few decades have been getting the benefits of using technology in education. In recent time in the Covid 19 situation, the education is provided through online from the primary to the higher education level in many countries. Bangladesh government also has tried to telecast online classes and recorded classes on Bangladesh Television and other various social media. The Public and Private universities have also conducted classes from their respective places through Zoom, Google Meet, Facebook Live, and YouTube and so on. Here a noticeable progress occurred in the private universities in spite of having some challenges. As a faculty member of a private university, the researcher has got some experiences while teaching at university. From this concern the researcher has got the interest on conducting research on the private university students and teachers to check the real scenario of online teaching and learning here in Bangladesh. This research is a quantitative in nature and questionnaire survey would be conducted for collecting data for analysis and finding out the real information. The main focus of this research is to find out the challenges and prospects of online education of the Department of English in the private universities in Bangladesh. JEL Classification Codes: H75.